RECONSTRUCTION OF PESANTREN MANAGEMENT MODEL: INTEGRATING CHARISMATIC AUTHORITY AND ORGANIZATIONAL PROFESSIONALISM - Muhammad Nur Kholis; Busro Karim; Rahmatullah; Hasan Zülfikar (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
Pesantren are currently navigating a critical intersection between preserving their traditional heritage, which is deeply rooted in the Kiai's charismatic authority, and meeting modern educational demands for professional governance and accountability. This study aims to conceptually reconstruct a management model that synergizes this personalistic leadership with organizational professionalism without eroding the institution's distinct spiritual identity. Employing a qualitative library research method, the study systematically analyzes academic literature published between 2016 and 2026 using content and thematic analysis to build a new theoretical foundation. The findings demonstrate that the dichotomy between tradition and modern bureaucratic standards can be effectively bridged through a Hybrid Management Model. This model functions through a strategic symbiosis that positions the Kiai as the central moral guardian and strategic visionary, while a professional management team executes daily operations utilizing formal Planning, Organizing, Actuating, and Controlling functions. This approach successfully mitigates organizational risks such as bureaucratic inefficiency, structural dependency, and unethical pro-organizational behavior. Ultimately, this proposed hybrid architecture ensures that pesantren can achieve measurable professional integrity, resolve leadership succession challenges, and remain highly competitive within the national education system while authentically preserving their traditional religious values. Keywords: Pesantren Management; Charismatic Authority; Organizational Professionalism; Hybrid Management Model;     Abstrak Saat ini, pesantren tengah berada di persimpangan kritis antara upaya melestarikan warisan tradisional yang berakar kuat pada otoritas karismatik Kiai, dengan tuntutan pendidikan modern akan tata kelola profesional dan akuntabilitas. Penelitian ini bertujuan untuk merekonstruksi secara konseptual model manajemen yang mensinergikan kepemimpinan personalistik tersebut dengan profesionalisme organisasi tanpa mengikis identitas spiritual institusi yang khas. Dengan menggunakan metode penelitian pustaka kualitatif, studi ini menganalisis literatur akademik yang diterbitkan antara tahun 2016 dan 2026 secara sistematis menggunakan analisis isi dan tematik untuk membangun landasan teoretis baru. Temuan menunjukkan bahwa dikotomi antara tradisi dan standar birokrasi modern dapat dijembatani secara efektif melalui Model Manajemen Hibrida. Model ini berfungsi melalui simbiosis strategis yang menempatkan Kiai sebagai penjaga moral pusat sekaligus visioner strategis, sementara tim manajemen profesional mengeksekusi operasional harian menggunakan fungsi formal Perencanaan (Planning), Pengorganisasian (Organizing), Penggerakan (Actuating), dan Pengawasan (Controlling). Pendekatan ini berhasil memitigasi risiko organisasi seperti inefisiensi birokrasi, ketergantungan struktural, dan perilaku pro-organisasi yang tidak etis. Pada akhirnya, arsitektur hibrida yang diusulkan ini memastikan bahwa pesantren dapat mencapai integritas profesional yang terukur, menyelesaikan tantangan suksesi kepemimpinan, dan tetap kompetitif dalam sistem pendidikan nasional sambil tetap menjaga nilai-nilai agama tradisional secara autentik. Kata Kunci: Manajemen Pesantren; Otoritas Karismatik; Profesionalisme Organisasi; Model Manajemen Hibrida.